Factors Influencing Adherence to Physiotherapy Appointments for Children with Cerebral Palsy at Chilenje Hospital in Zambia: A Mother's Perspective (2017-2018) - Dorcas Foto; Geoffrey Moyo; Brian Chanda Chiluba (Indonesian Journal of Disability Studies, 2021)
Adherence to treatment appointments by mothers of children with Cerebral Palsy is one of the factors affected in rehabilitation of a child with Cerebral Palsy, and this is cardinal to ensure effective rehabilitation outcomes for the child. Hence this study aimed to explore the factors influencing poor adherence to physiotherapy appointments by mothers of children with Cerebral Palsy at Chilenje Hospital, in Lusaka. A qualitative case study design utilising a phenomenological approach was conducted with a sample of 12 mothers of children with Cerebral palsy from Chilenje Hospital, Lusaka. Convenient sampling was utilized where mothers who were non-adhering were also purposefully selected into the study to better understand the factors affecting adherence to physiotherapy. The factors that contributed to caregivers defaulting scheduled therapy included economic constraints like unemployment and low education level, caregiver related factors such as marital challenges, and service centered factors such as challenges with the diagnosis of Cerebral Palsy and negative clinician attitudes. Majority of the caregivers admitted that they were motivated to attend therapy by observable improvements in their children. A combination of psychosocial, economic, child centered and service centered factors contributed to caregivers defaulting scheduled therapy. Interventions that may potentially improve caregiver attendance to scheduled therapy include community outreach services, efficient rehabilitation service provision at the hospitals, and facilitation of income generating programmes for mothers and caregivers.